Ecological characterization of wild Helianthus annuus and H. petiolaris germplasm in Argentina - Poverene, Maria Monica (2009)
Helianthus annuus and H. petiolaris (Asteraceae) are wild sunflowers native to North America but have become naturalized in central Argentina covering an area of about 5 million hectares. Wild H. annuus has been recognized as invader species in several countries, but no research has been done to study the ecological determinants of their distribution. In a survey covering seven provinces between 318580 –388S and 608330 –698W, we described the ecology of the main wild populations. Wild Helianthus populations were located in three of the 18 ecological regions of Argentina, on five Mollisol and seven Entisol soil groups. The associated plant communities were comprised 60 species belonging to 16 families, all being frequent components of the native flora. Disease symptoms were seldom observed in wild populations, with Alternaria helianthi being the most commonly observed pathogen. Population size varied from less than 100 to more than 100,000 plants, covering from 100 to more than 60,000 m2 with densities most frequently up to 3 plants/m2 , but reaching 80 plants/m2 at certain sites. Intermediate plant phenotypes between wild species and cultivated sunflower were found in one-third of the populations providing evidence of intense gene flow. Hybrid swarms were found at three localities with population sizes between 100 and 10,000 individuals.